2013
DOI: 10.1089/jir.2012.0080
|View full text |Cite
|
Sign up to set email alerts
|

Type I and Type II Interferons Inhibit Both Basal and Tumor Necrosis Factor-α-Induced CXCL8 Secretion in Primary Cultures of Human Thyrocytes

Abstract: Interferons (IFNs) and tumor necrosis factor-α (TNF-α) cooperate in activating several inflammation-related genes, which sustain chronic inflammation in autoimmune thyroid disease (AITD). Much is known about the positive signaling of IFNs to activate gene expression in AITD, while the mechanisms by which IFNs negatively regulate genes remain less studied. While IFNs inhibit CXCL8 secretion in several human cell types, their effects on thyroid cells were not evaluated. Our aim was to study the interplay between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Compounds with anti-BRAF kinase activity were successfully tested for their ability to block CXCL8 synthesis in melanoma cell lines harboring the BRAFV600E mutation [20]. In addition, besides type I and Type II interferons which were previously shown to inhibit the secretion of CXCL8 [13,15], other potentially interesting molecules to be tested for their CXCL8 inhibiting effects could include PPAR-c agonists. This appears to be supported by the evidences provided by Antonelli et al who reported that PPAR-c agonists display antineoplastic activity [25,26] and inhibit the secretion of several chemokines in primary cultures of thyroid cancer cells [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds with anti-BRAF kinase activity were successfully tested for their ability to block CXCL8 synthesis in melanoma cell lines harboring the BRAFV600E mutation [20]. In addition, besides type I and Type II interferons which were previously shown to inhibit the secretion of CXCL8 [13,15], other potentially interesting molecules to be tested for their CXCL8 inhibiting effects could include PPAR-c agonists. This appears to be supported by the evidences provided by Antonelli et al who reported that PPAR-c agonists display antineoplastic activity [25,26] and inhibit the secretion of several chemokines in primary cultures of thyroid cancer cells [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CXCL8 enhances the secretion of growth factors by tumor-associated macrophages, which in turn further increase the rate of tumor cell proliferation and also play a role in the angiogenic and metastatic potential of many solid cancers [2][3][4]. For these reasons, the interest for further advances in the understanding of CXCL8 regulation as well as in CXCL8 targeting and/or inhibition has rapidly grown in recent years [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“… 247 Moreover, TNF-α-induced CXCL8 secretion may be inhibited by IFNs in human thyrocytes, suggesting different roles for CXCL10 and CXCL8 in thyroid disease. 248 Recent studies have demonstrated that CXCL10 may be involved in the initial phase of GD, while CXCL8 may be involved in a later chronic phase of GD. 249 In addition, CXCL8 was found to be increased in streptozocin-induced diabetic mice, whereas the inhibition of CXCL8 had a therapeutic effect in improving renal histopathology in diabetic nephropathy.…”
Section: Environmental Factors and Autoimmunitymentioning
confidence: 99%
“…Interesting results were found not only by targeting these two receptors, but also by modulating the secretion of one of their ligands, CXCL8, a chemokine which binds both CXCR1 and CXCR2. By using different compounds, it was demonstrated that the inhibition of CXCL8 secretion in thyroid cancer cells reduces cell migration in in vitro experiments (Rotondi et al 2013, Awwad et al 2018, Coperchini et al 2019. Accordingly, thyroid cancer metastasis is reduced and survival is prolonged in animal models (Fang et al 2014).…”
Section: Chemokine Receptors and Immunotherapymentioning
confidence: 99%